Interrelationship of Vocabulary and Grammar Mastery in Shaping Descriptive Writing Competence: An Applied Linguistics Perspective on High School Students - Shohibatil Karomah; Nurul Hadi; Anees El Zer (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2025)
his research aims to determine the relationship between vocabulary mastery and grammar proficiency on the descriptive writing skills of second-grade students at the Islamic High School of Miftahul Qulub in Polagan. This study is a post-facto research involving a sample of 40 students. Data were collected through tests measuring vocabulary and grammar mastery, as well as descriptive writing ability. The data analysis techniques employed include product-moment correlation analysis and multiple linear regression analysis, with a significance level set at 5%. The findings reveal: (1) a positive and significant relationship between vocabulary mastery and descriptive writing ability, with a correlation coefficient of 0.445; (2) a positive and significant relationship between grammar mastery and descriptive writing ability, with a correlation coefficient of 0.554; (3) a positive and significant relationship between vocabulary and grammar mastery combined on descriptive writing ability, with a value of 12.225 and a regression coefficient of 0.631. This indicates that the higher the students’ mastery of vocabulary and grammar, the better their ability to write descriptive texts. This finding reinforces the theory that language proficiency serves as a crucial foundation in developing productive skills such as writing, and contributes to the development of Arabic writing instruction strategies that emphasize systematic mastery of linguistic elements.